Analisis Perhitungan Biaya Lingkungan Atas Pengelolaan Limbah Padat Covid-19 dalam Mencapai Eco-Efficiency (Studi Kasus pada RSUP Dr. Hasan Sadikin Bandung) - Vita Alifah Maulina; Arie Apriadi Nugraha; Jouzar Farouq Ishak (Indonesian Accounting Literacy Journal, 2022)
Environmental issues need to be considered by all agencies because every operational activity will produce waste which if not managed properly can cause environmental problems. During the pandemic, health service especially hospitals, experienced an increase in its waste due to Covid-19 handling activities one of the referral hospitals is Hasan Sadikin General Hospital. Analysis of environmental cost calculations can be carried out to find out how hospital manage the environment for Covid-19 waste and how much costs are incurred for these activities to achieve environmental efficiency (eco-efficiency) at the hospital. This study uses a qualitative method with Miles&Hubberman data analysis technique. The results indicate that the calculation of environmental costs produces a percentage of 1.68% of the total operational costs in 2021. This reflects that Covid-19 solid waste management at Hasan Sadikin General Hospital has achieved eco-efficiency, especially in terms of financial benefits which will affect a better company image.